Development of Science Learning Media Assisted by Augmented Reality Based on the Problem Based Learning (PBL) Model to Improve Critical Thinking Skills of Elementary School Students - Salmiyanti (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an Augmented Reality (AR)-assisted science learning media based on the Problem Based Learning (PBL) model to improve critical thinking skills of fourth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the study were 72 students from three elementary schools in Padang City, namely SDN 09 Korong Gadang, SDN 04 Pasar Ambacang, and MIN 3 Padang City. Data collection instruments included expert validation sheets, teacher and student practicality questionnaires, and pre-test and post-test questions. The results of the study showed: the validity of the media was assessed as very valid by language experts (92%), material experts (97%), and media experts; the practicality of the media was very practical according to teacher (96%) and student (95.64%) assessments; The effectiveness of the media is proven by the increase in student learning outcomes with an average pre-test of 59.31 increasing to 92.11 in the post-test, with an N-Gain value of 0.81 in the high category. It is concluded that PBL-based AR learning media is feasible, practical, and effective for use in improving the critical thinking skills of fourth grade elementary school students in the Science subject of the Five Senses material, in accordance with the demands of the Independent Curriculum.